2019
DOI: 10.20524/aog.2019.0381
|View full text |Cite
|
Sign up to set email alerts
|

Azathioprine dosing and metabolite measurement in pediatric inflammatory bowel disease: does one size fit all?

Abstract: Background Azathioprine is widely used for the maintenance of remission in children with inflammatory bowel disease (IBD). Measuring thiopurine metabolites 6-thioguanine (6-TGN) and 6-methyl-mercaptopurine (6-MMP) can aid in optimizing treatment and preventing toxicity. We report a proactive approach combining early metabolite measurements with IBD activity index to achieve optimal azathioprine dosing. Methods The reporting of azathioprine dosing, IBD activity indexes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
(34 reference statements)
2
2
0
Order By: Relevance
“…None of the children developed azathioprine toxicity, as defined by abnormal liver function tests. That observation was similar to that in another study [ 26 ]. On the contrary, Pavlovska et al reported a higher percentage of adverse effects [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…None of the children developed azathioprine toxicity, as defined by abnormal liver function tests. That observation was similar to that in another study [ 26 ]. On the contrary, Pavlovska et al reported a higher percentage of adverse effects [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…As in some other studies, we did not find any correlation between thiopurine dose and 6-TGN levels; therefore, increasing the drug dose may not be sufficient to reach the desired 6-TGN target [ 24 , 26 ]. This may be explained by an increased methylation of intermediate 6-MP metabolites by inherited high levels of TPMT activity [ 5 ].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Out of 41 pediatric patients evaluated in one retrospective study conducted in England, 12 patients required dose increases to achieve clinical remission. A total of 28 patients did not require AZA dose adjustments and achieved [ 142 ].…”
Section: Empiric Therapiesmentioning
confidence: 99%